The carotenoid‐based red cap of the Middle Spotted Woodpecker Dendrocopos medius reflects individual quality and territory size. (29th April 2013) - Leniowski, Konrad; Węgrzyn, Ewa; Fuchs, Jerome
<x xml:space="preserve">Abstract</x> Carotenoid‐based plumage ornaments have the potential to signal individual condition and health in many species of birds. However, very little is known about the function of red plumage in woodpeckers. We assessed whether the red cap displayed by both male and female Middle Spotted Woodpeckers reflects individual quality, finding that the size of the cap is sex‐dependent, whereas the brightness of the cap correlates with the body condition of an individual. Furthermore, birds with brighter caps had larger clutches, suggesting that cap coloration may be an honest signal of parental quality in woodpeckers. Interestingly, more colourful individuals also occupied smaller territories, suggesting that territory size and territory quality may be inversely related in the Middle Spotted Woodpecker.